﻿Essential oil in Phlomis tuberosa - Aleksandar Shkondrov; Aleksandra Ivanova; Magdalena Kondeva-Burdina; Ilina Krasteva (Pensoft Publishers, 2023)
Phlomis tuberosa L. (Lamiaceae) is a flowering perennial plant, native to Eurasia, and sparsely distributed in Bulgaria. The species has been proved to accumulate flavonoids, iridoids, phenolic glycosides, as well as essential oil. To now, there is no information on the chemical content of Bulgarian essential oil from the plant. The aim was to study the chemical composition of essential oils, obtained from the species. Four different samples were studied - essential oils produced from leaves and herbs, collected in the fields, and from leaves and flowering parts, harvested from the mountainous location. It was found that β-copaene was the major in the essential oil from both the leaves and of the flowering parts collected from Popitza. In addition, the other major constituent in leaf essential oil from Kladnitza was tau-muurolol. The essential oil, produced from the species, harvested from the higher altitude had phytol as the main component. The sesquiterpenoid content in leaf essential oil suggests that this plant substance is appropriate for medicinal use, due to the pharmacological properties of these compounds.